2014
DOI: 10.2478/s11756-014-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water stress and NaCl triggered changes on yield, physiology, biochemistry of broad bean (Vicia faba) plants and on quality of harvested pods

Abstract: Salinity and drought are the most important abiotic stresses affecting crop yield. Broad bean was chosen as model plant for assessing the impact of salt stress and its interaction with drought in the field experiments. The factors examined in the experiments were the two irrigation rates (normal watering -NW with 3 L plant −1 and drought -D) and three salinity rates imposed by foliar application (0, 50, 100 mg L −1 NaCl). Highest NaCl level with normal water irrigation caused maximum reduction in plant height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…The highest number of pods and seeds per plant showed by minor type followed by equina under well irrigation but equina genotypes were maintained numbers of pods in stress conditions (9.8, 7.1 and 6.8 for Hassawi 2, Giza 843 and Giza 2, respectively) but as mean of the water treatments suggested the superior of TW, Hassawi 2 and Gazira 2 with maximum number of pods (15.2, 13.8 and 13.5, respectively). Concerning no of seeds/plant, minor type genotypes produced highest number under well-watered conditions however, under drought stress Hassawi 2 from equina type shared Gazira 2 the first rank with mean number of 16.0 and 15.3, respectively (Table 4).These results are in agreement with these obtained by Khalafallah et al (2008), Ouzounidou et al (2014), Ammar et al (2014) and Alghamdi et al (2014) found that drought stress significantly influenced all faba bean characters. , source of variation; d.f., degree of freedom; ns, non-significant;*Significant at P 0.05; **Significant at P 0.01.…”
Section: Resultssupporting
confidence: 90%
“…The highest number of pods and seeds per plant showed by minor type followed by equina under well irrigation but equina genotypes were maintained numbers of pods in stress conditions (9.8, 7.1 and 6.8 for Hassawi 2, Giza 843 and Giza 2, respectively) but as mean of the water treatments suggested the superior of TW, Hassawi 2 and Gazira 2 with maximum number of pods (15.2, 13.8 and 13.5, respectively). Concerning no of seeds/plant, minor type genotypes produced highest number under well-watered conditions however, under drought stress Hassawi 2 from equina type shared Gazira 2 the first rank with mean number of 16.0 and 15.3, respectively (Table 4).These results are in agreement with these obtained by Khalafallah et al (2008), Ouzounidou et al (2014), Ammar et al (2014) and Alghamdi et al (2014) found that drought stress significantly influenced all faba bean characters. , source of variation; d.f., degree of freedom; ns, non-significant;*Significant at P 0.05; **Significant at P 0.01.…”
Section: Resultssupporting
confidence: 90%
“…The highest and lowest reductions were observed in shoot fresh weight (~7 fold) and leaf width (~2 fold), respectively, relative to the control plants. A similar reduction in growth parameters under high NaCl concentration was also observed in a number of other plants, including lettuce [6,9,24,[33][34][35][36]. Qin et al [32] also found a significant reduction in lettuce fresh weight, grown under higher saline concentrations than controls.…”
Section: Effect Of Nacl Concentration In Plant Growth Parameterssupporting
confidence: 57%
“…Drought stress increased protein concentrations in chickpea shoot (Rai et al, 1983), the whole barley plant (Bole and Pittman, 1978), in tomato leaves (Chao et al, 1999), and in the alfalfa shoot (Aranjuelo et al, 2011). However, levels of protein were reduced in immature and mature pods of broad bean (Ouzounidou et al, 2014), leaves of common bean (Lazcano-Ferrat and Lovatt, 1999), the wheat plant (Kulshrestha et al, 1987) and in shoots and roots of rice (Sharma and Dubey, 2005).…”
Section: Discussionmentioning
confidence: 99%